Hubungan Penggunaan Zoom Untuk Pembelajaran Daring Era Pandemi Covid-19 Terhadap Motivasi Belajar Mahasiswa Program Studi Pendidikan Akuntansi - Varidhatul Aylina; Fransisca Novelia Pute Nudek; Indah Verawati Matondang (Jurnal Pendidikan Akuntansi (JPAK), 2021)
Covid-19 pandemic has influenced educational system in Indonesia. It changes conventional learning into online learning. Despite the internet and classroom management challenges, zoom is widely used to facilitate the learning process in the higher education. This study aims to examine the influence of using zoom for online learning on students’ motivation. The research participants were 45 students at Sanata Dharma University. Quantitative research method was employed by using online-based questionnaire with 5-point Likert scale: strongly disagree (1) to strongly agree (5). The Spearman correlation test shows that the experience of using zoom as learning medium is significantly related to students’ learning motivation.